The carriage of interleukin-1B-31*C allele plus Staphylococcus aureus and Haemophilus influenzae increases the risk of recurrent tonsillitis in a Mexican population - Borrow, Ray; González Andrade, Baltazar; Santos Lartigue, Ramiro; Flores Treviño, Samantha Maribel; Ramirez Ochoa, Natalie Sonia; Bocanegra Ibarias, Paola; Huerta Torres, Francisco J.; Mendoza Olazarán, Soraya Sarahí; Villarreal Treviño, Licet; Camacho Ortiz, Adrián; Villarreal Vázquez, Hipólito; Garza González, Elvira (2017)
Abstract The aim of the present study was to estimate the relative contribution of immunogenetic and microbiological factors in the development of recurrent tonsillitis in a Mexican population. Patients (n = 138) with recurrent tonsillitis and an indication of tonsillectomy (mean age: 6.05 years±3.00; median age: 5 years, female: 58; age range: 1–15 years) and 195 nonrelated controls older than 18 years and a medical history free of recurrent tonsillitis were included. To evaluate the microbial contribution, tonsil swab samples from both groups and extracted tonsil samples from cases were cultured. Biofilm production of isolated bacteria was measured. To assess the immunogenetic component, DNA from peripheral blood was genotyped for the TNFA-308G/A single-nucleotide polymorphism (SNP) and for the IL1B -31C/T SNP. Normal microbiota, but no pathogens or potential pathogens, were identified from all control sample cultures. The most frequent pathogenic species detected in tonsils from cases were Staphylococcus aureus (48.6%, 67/138) and Haemophilus influenzae (31.9%, 44/138), which were found more frequently in patient samples than in samples from healthy volunteers (P<0.0001). Importantly, 41/54 (75.9%) S. aureus isolates were biofilm producers (18 weak and 23 strong), whereas 17/25 (68%) H. influenzae isolates were biofilm producers (10 weak, and 7 strong biofilm producers). Patients with at least one copy of the IL1B-31*C allele had a higher risk of recurrent tonsillitis (OR = 4.03; 95% CI = 1.27– 14.27; P = 0.013). TNFA-308 G/A alleles were not preferentially distributed among the groups. When considering the presence of IL1B-31*C plus S. aureus, IL1B-31*C plus S. aureus biofilm producer, IL1B-31*C plus H. influenzae or IL1B-31*C plus H. influenzae biofilm producer, the OR tended to infinite. Thus, the presence of IL1B-31*C allele plus the presence of S. aureus and/or H. influenzae could be related to the development of tonsillitis in this particular Mexican population.